An experimental analysis of the onset of buckling in sheet metal forming. (4th August 2014) - Sobis, T.; Engel, U.; Geiger, M.
In this study a test method is presented in which buckling phenomena can be investigated at a fundamental level. A rectangular sheet sample is fixed in a specially designed mounting device which transfers tensile forces in the longitudinal direction as well as compressive forces in the perpendicular direction. The mechanical principle used ensures a steady ratio of the corresponding strains. Onset and growth of the wrinkle can be monitored by special measuring equipment. The aim of the experimental and theoretical investigations described in this paper was to check the operational characteristics and capabilities of the equipment and to deduce a reproducible criterion for the formation of wrinkles.